Explanation in psychology : towards a singular causal theory - Braun, Ricardo (2000)
The problem of scientific explanation in general and in psychology in particular is analized from a philosophical standpoint. The central thesis is that causality is causality is a necessary component of explanations. The impact of the hempelian model on psychology is revisited and the author suggests that under that model, psychology as a science is discarted. A non-causal model of explanation is discussed and shown to be inadequate as a form of explanation. Finally, a theory of singular causation is suggested as a model for psychological explanations.